The Effect of bisphenol A and Photobiomodulation Therapy on Autophagy-Related Genes Induction in Adipose Tissue-Derived Stem Cells: Effects of Bisphenol A and Photobiomodulation Treatments on Autophagy - Ebrahimi-kia, Yasaman; Noori-Zadeh, Ali; Rajaee, Farzad; Darabi, Shahram; Darabi, Leila; Ghasemi Hamidabadi, Hatef (Journal of Lasers in Medical Sciences, 2022)
Introduction: As adipose tissue-derived stem cells (ADSCs) can divide rapidly and be prepared noninvasively, they have extensively been used in regenerative medicine. On the other hand, a new method of therapy, known as photobiomodulation (PHT), has been used to treat many diseases, such as inflammatory conditions, wound healing and pain. Besides, exposure to chemical substances such as bisphenol A (BPA), at low levels, can lead to autophagy. This study investigated the effects of BPA and PHT on the expression of autophagy-related genes, including LC3, NRF2, and P62, in rat ADSCs as a model. Methods: ADSCs isolation and purification were confirmed by immunocytochemistry (ICC). The cells were then treated with different concentrations of BPA and also subjected to PHT. Reverse transcription polymerase chain reaction (RT-PCR) was used for the evaluation of LC3, NRF2 and P62 gene expressions. Oil red O staining was used for adipogenic vacuole formation. Result: ICC showed that the isolated cells were CD 49-positive but CD 31 and CD 34-negative. The viability test indicated that the number of live cells after 24 hours in the BPA groups at concentrations of 0, 1, 50, 100 and 200 μM was 100%, 93%, 81%, 72%, and 43% respectively. The difference in cell viability between groups 50, 100 and 200 μM was significant as compared with the control groups (P<0.05). Moreover, in the group with 1 μM concentration of BPA, the expressions of LC3, NRF2 and P62 genes were upregulated. However, in the treatment group at the concentration of 200 μM of BPA, the LC3 gene was expressed, but NRF2 and P62 genes were downregulated. Conclusion: BPA and PHT induce autophagy and adiposeness in ADSCs in a dose-dependent manner. Doi:10.34172/jlms.2022.15.